Uji Aktivitas Antioksidan Mikroalga Air Tawar - Rio Kristian; Sapto Raharjo; Sulastrianah Sulastrianah (Halu Oleo University, 2015)
Cell or tissue damage due to oxidative stress can be slowed by giving antioxidants. Antioxidants are vital substances that may help protect the body against free radicals by neutralizing or mitigate negative impacts. The human body is naturally equipped antioxidant defenses. but these antioxidants can not completely prevent cell damage. Body still requires antioxidants from the outside. The purpose of this study was to determine the antioxidant potential of microalgae species in freshwater.This research is a descriptive study of the identification of species of freshwater microalgae samples taken with a microscope and testing of extracts from freshwater microalgae species of antioxidant activity using DPPH method. Microalgae extract as much 2,25ml then homogenized with DPPH as 0,75ml in containers with a volume of 3ml. The containers are then incubated for 30 minutes in a dark room. Furthermore, the container is inserted into the spectrophotometer to read absorbance at 519nm wavelength. Results absorbance at the input curves to obtain IC50 values.The results that have identified three species of freshwater microalgae namely Navicula sp., Oscillatoria sp., And Carteria sp. From all three species showed strong inhibition against DPPH with IC50 values sequentially 41.304 ppm, 23.401 ppm and 51.433 ppm. The conclusions of this study are species of freshwater microalgae are obtained, namely Navicula sp., Oscilatoria sp., And Carteria sp. has potential antioxidant activityKeywords: Microalgae, antioxidant, DPPH